Dyslipidemia, Hypertension and Diabetes Metaflammation: A Unique Mechanism for 3 Risk Factors - Morales-Villegas, Enrique (Current Hypertension Reviews, 2013)
The main current threat to the human race is the correlation and synergy between two determining triumvirates of atherosclerosis, cardiovascular disease and death. The first triumvirate is constituted by obesity, metaflammation and insulin resistance; the second triumvirate is constituted by atherogenic dyslipidemia, hypertension and type 2 diabetes mellitus. The etiopathogenic driving force for both triumvirates is the global epidemic of obesity. Metaflammation and insulin resistance are associated with obesity; in turn, insulin resistance determines a high risk for the development of atherogenic dyslipidemia, hypertension and type 2 diabetes mellitus, the three of them being factors responsible for vascular endothelial injury and substrates involved in the genesis of atherosclerosis, cardiovascular disease and death. The present chapter will address both triumvirates. Firstly, the current concepts of obesity, metaflammation and insulin resistance will be reviewed; emphasizing the second (metaflammation) for being a concept that has revolutionized and integrated our understanding of the harmful effects of obesity. Secondly, the impact of insulin resistance in the regulation of intermediary metabolism and endothelial function will be addressed; this will facilitate the understanding of the inextricable link between atherogenic dyslipidemia, hypertension and type 2 diabetes mellitus. Thus, this chapter aims to present to the clinician the best knowledge to link epidemics of obesity and cardiovascular death, through the sequence of metaflammation, insulin Atherogenic-dyslipidemia, atherosclerosis, cardiovascular-disease, diabetes-mellitus, hypertension, insulinresistance, metaflammation, obesity.resistance and cardiovascular risk factors (mixed dyslipidemia, hypertension and type 2 diabetes mellitus).
Keywords: obesity